Interplay between viral infections and genetic alterations in liver cancer - Hainaut, Pierre (Iatreia, 2007)
With over 500 000 annual deaths, Hepatocellular carcinoma (HCC) is the fifth most common cancer worldwide and a leading cause of death in developing countries where about 80% of the cases arise. Risk factors include chronic hepatitis infections (hepatitis B, (HBV) and hepatitis C (HCV) viruses), alcohol, dietary contaminants such as falatoxins The incidence shows important geographic variations, accor In southern Asia, HCC development is mainly related to the endemic Hepatitis B Virus (HBV) infection, cases with hot spot mutation in codon 249 (249ser) of TP53 tumor suppressor gene were also described and associated to a low-intermediate exposure rate to Aflatoxin B1 (AFB1). Presence of Hepatitis C Virus (HCV) infection was also detected in 12 - 17% of HCC cases. Despite the increasing number of studies identifying viral/host interactions in viro-induced HCC or describing potential pathways for hepatocarcinogenesis, precise mechanism has not been identified so far. HBV was demonstrated to enhance hepatocarcinogenesis by different manners; HBV chronic infection is associated to active hepatitis (CAH) and cirrhosis which are hepatic complications considered as early stage for HCC development. These complications mobilise the host immune response, the resulting inflammation initiates and selects the first genetic alteration at the origin of loss of cell control. Moreover, HBV can also promote carcinogenesis through genetic instability generated by its common integration in host DNA. HBV proteins, as HBx, was proven to interact with a variety of targets in the host cell including protein or host transcription factor such as, in particular, the p53 protein or the transcription factor E4F, which is implicated in growth, differenciation and senescence. Specific HBV mutations or distinct HBV genotypes are associated to higher risks factors for HCC or hepatic complications leading to HCC. In summary, active HBV replication potentially disrupts gene integrity, may lead to oncogenic activation through several parallel mechanism, and the role of each of these mechanism may vary with the molecular diversity of viral genotypes.